Nouvelles sources de la peur dans le récit néofantastique de Jean-Pierre Andrevon - Gadomska, Katarzyna (Romanica Silesiana)
The purpose of this article is to present new sources of fear in short fantastic stories of Jean-Pierre Andrevon. First, it is necessary to underscore the anxiogenic role of the Uncanny – the malaise born out of rupture in everyday life which was once reassuring. The paper discusses the discourses of space and body – both origins of the Uncanny penetrate each other, become in the indubitable report, follow the reciprocate, often regressive dynamic. The familiar space metamorphoses into the space of a scary and distended geometry; the healthy, normal body transforms into a strange and alien one; the fragmentation of the body designates the disintegration of the familiar space. In brief, short fantastic stories of JeanPierre Andrevon emphasize particularly the isotopic acuity of the fragmentation of the body and the fragmentation of the space. The topic is analyzed using psychoanalysis and, especially, psychoanalytic terms like the Uncanny, the return of the repressed and the mirror stage. Key words: fear, Uncanny, psychoanalysis, space, body, fantastic literature, Jean-Pierre Andrevon